Edukasi Pembuatan Pupuk Kompos di Desa Labissa Kecamatan Ajangale Kabupaten Bone - Ririn Eka; Andi Alwa; Suharni Sudirman; Rompegading, Andi Badli; Syamsu Rijal; Muhammad Nasir; Ahmad Yani; Rizal Irfandi; Muhammad Arafah (Education and Talent Development Center Indonesia, 2024)
This Compost Making Training will increase the knowledge and skills of the community to process and optimize existing Natural Resources (SDA) and Human Resources (SDM) in order to improve the economy of the Labissa Village community. This training activity on making compost was carried out in the Labissa Village Office Hall, Ajangale District, Bone Regency in December 2023. The tools used were tarpaulin, knife, shovel, hoe, gloves. The materials used are livestock (cow) manure, water, vegetable and fruit waste, soil, husks, brown sugar, brown (dry) and green leaves, catfish pond water starter, wood dust, coconut belt. After the question and answer process took place, there were 85% positive responses from approximately 25 participants, in this case the people of Labissa Village, Ajangale District, Bone Regency. The expected impact of this training is that the community will have broad insight into waste or organic waste so that they can process it into something useful and beneficial.